Support, image and writing in Celtiberian funerary inscriptions (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The funerary inscriptions in Celtiberian language constitute a scarce set of epigraphs, of a very heterogeneous typology and defective state of conservation. In this paper —after having increased the corpus of funerary incriptions with two unpublished inscriptions—, I pay special attention to the relationship between support, image and text, identifying typologies and proposing evolutionary lines, for which I make comparisons with the previous pre-literary state, represented by the stelae of the Celtiberian Iron Age necropoleis, on the one hand and with some Latin epigraphic types of the Celtiberian region, on the other.
Keywords: Celtiberian Language; Funerary Epigraphs; Discoidal Stelae; Decorated Stelae; Celtiberian Necropoleis